Worker representation and temporary employment in Germany: the deployment and extent of fixed-term contracts and temporary agency work - Addison, John T.; Teixeira, Paulino; Grunau, Philipp; Bellmann, Lutz (Bonn, 2018)
"This study examines the potential impact of works councils and unions on the deployment of fixed-term contracts and agency temps. We report inter al. that works councils are associated with a higher number of temporary agency workers when demand volatility is high while the opposite holds for fixed-term contracts. These disparities likely reflect differences in function, with agency work being more directed toward the protection of a shrinking core and fixed-term contacts being as much a port of entry as a buffer stock. We are also able to identify the number of new hires with a fixed-term contract as well as the number of FTC conversions (into regular employment) and renewals, the correlates of which flows are broadly consistent with the stock data."